Dependence of RF breakdown curve on electrode geometry in CCP reactor - Dudin, S.V.; Dakhov, A.N.; Lisovskiy, V.A.; Pletniov, V.M. (Вопросы атомной науки и техники, 2012)
The results of experimental and theoretical study of RF capacitively coupled discharge breakdown in reactor for reactive ion etching of semiconductors are presented. Taking into account complex geometry of the reactor with asymmetric electrodes the main attention has been paid to influence of geometric factor on the breakdown curve. Experiments have shown that the geometry of the electrodes has impact on the breakdown curve only at lowest gas pressure (<50 mTorr). In cylindrical configuration the curve has a region of ambiguity, while for asymmetric configuration similar to GEC reference cell the low pressure part of the breakdown curve is almost vertical. The experimental data are compared to the numerical simulation results obtained using the particle-in-cell/Monte Carlo (PIC/MCC) code. The comparison shows qualitative consistence of the results with general tendency of theoretical curves to be slightly shifted to higher pressures that can be explained by simultaneous action of different kinds of electron emission from the electrodes, while we accounted only for secondary electron emission. Both theory and experiment show influence of secondary electron yield from different electrode materials (aluminum, steel, graphite) on the low-pressure part of the breakdown curve.